2008
DOI: 10.1074/jbc.m803440200
|View full text |Cite
|
Sign up to set email alerts
|

Follistatin-like 1, a Secreted Muscle Protein, Promotes Endothelial Cell Function and Revascularization in Ischemic Tissue through a Nitric-oxide Synthase-dependent Mechanism

Abstract: The stimulatory effect of Ad-Fstl1 on ischemic limb reperfusion was abolished in mice lacking eNOS. These data indicate that Fstl1 is a secreted muscle protein or myokine that can function to promote endothelial cell function and stimulates revascularization in response to ischemic insult through its ability to activate AkteNOS signaling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
249
2
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 273 publications
(270 citation statements)
references
References 37 publications
(44 reference statements)
11
249
2
3
Order By: Relevance
“…We previously reported several factors secreted by muscle that are increased by Akt1 overexpression. 18,43 In the UUO model, we found that myogenic activation of Akt upregulated serum levels of stromal cell-derived factor-1, IL-10, and IL-17, which are known to activate eNOS. 44,45 Further studies will be required to determine whether these factors are involved in renal eNOS activation and renoprotective properties of Akt1-mediated skeletal muscle growth.…”
Section: Discussionmentioning
confidence: 96%
“…We previously reported several factors secreted by muscle that are increased by Akt1 overexpression. 18,43 In the UUO model, we found that myogenic activation of Akt upregulated serum levels of stromal cell-derived factor-1, IL-10, and IL-17, which are known to activate eNOS. 44,45 Further studies will be required to determine whether these factors are involved in renal eNOS activation and renoprotective properties of Akt1-mediated skeletal muscle growth.…”
Section: Discussionmentioning
confidence: 96%
“…Most interestingly, it is upregulated via Akt signalling. Ouchi et al have proposed that FSTL1 can be designated as a myokine that acts on vascular endothelial cells [130]. In murine skeletal muscle, overexpression of FSTL1 was shown to promote endothelial cell function and revascularisation in ischaemic tissue.…”
Section: Key Facts: Myokines As Therapeutic Targetsmentioning
confidence: 99%
“…However, skeletal muscle is not the only tissue to express and release FSTL1. Proteomic approaches have identified FSTL1 in the supernatant fraction of primary human adipocytes [132], in the supernatant fraction of human endothelial cells [130] and in lysates of murine cardiac myocytes [133].…”
Section: Key Facts: Myokines As Therapeutic Targetsmentioning
confidence: 99%
“…Secreted by skeletal muscle fiber in response to exercise, IL-6 has been shown to improve whole-body insulin sensitivity and dampen inflammation, providing a link between exercise and the improvement in systemic metabolic parameters (15,16). In mice, skeletal muscle-derived Fstl-1 promotes endothelial cell function and revascularization in ischemic tissue (10). Elevated serum levels of IL-15 via transgenic expression in mouse skeletal muscle reduce fat mass and decrease adiposity in response to high-fat feeding (13).…”
mentioning
confidence: 99%